Fragile: teorias de controle e a decolonização performativa do corpo dissidente - Dias, Cristiane Peres (2022)
The bodies of racialized women carry stereotypes that participate in colonialist narratives structured by the associative relations between race, gender, and class, a triad commonly exerted by coercive practices that affect their identities in the social disposition. Performance art activated by Black women's bodies is one of the manifestations of contemporary art that makes it possible to strain imposing patterns that seek to establish where and how these bodies should exist. This research aims to analyze how Black performance art can dispute theories of coloniality control through the decolonization of theoretical and practical knowledge raised by issues related to the racist experiences of black women. I examine three photographic records of the performance entitled Fragile (1/25), photographed by me, held in the interior of Pernambuco, in 2021, during an artistic residency at “Usina de Arte.” In the analyses, I emphasize the confrontations experienced by dissident bodies facing the processes of genderized racism, intersected by cultural erasures and identity trauma as products of structural racism. It is qualitative research (Guerra, 2014), with a case study (Yin, 2011), literature review, documental analysis, and autobiography mediated by decolonial knowledge. The studies were articulated from visual productions of black Brazilian artists and a brief history of the racialized body, as a vehicle of historical and interdisciplinary knowledge, based on Taylor (2013) and Ligiéro (2011). I approach the practices of coercion and identity disintegration through the unnatural theories of whitening, and the policies of inequality from the point of view of Carneiro (2011), Schwarcz (2012), and Fanon (2019). The intellectuals Kilomba (2019), Davis (2016), Collins (2019), hoocks (2020), and Gonzalez (2020) bring to light the narrative decolonization of race, gender, and class relations of the racialized and female body in its anachronistic diversity. The research highlights the Black art performance as a theoretical-expressive conduit of decolonized knowledge, articulated by experiences and performativities dissidents to the colonizing limits.